Chemical Exchange Saturation Transfer Magnetic Resonance Imaging for Longitudinal Assessment of Intracerebral Hemorrhage and Deferoxamine Treatment at 3T in a Mouse Model. Issue 1 (23rd November 2022) - Lai, Joseph H.C.; Liu, Jiaxin; Yang, Tian; Huang, Jianpan; Liu, Yang; Chen, Zilin; Lee, Youngjin; Leung, Gilberto K.K.; Chan, Kannie W.Y.
Abstract : Background: Noninvasive imaging of molecular alterations after intracerebral hemorrhage (ICH) could provide valuable information to guide and monitor treatments. Chemical exchange saturation transfer (CEST) magnetic resonance imaging has demonstrated promises in identifying proliferation, necrosis, and changes in cellularity in brain tumors. Here, we applied CEST magnetic resonance imaging to monitor molecular changes in hematoma without and with treatment noninvasively over 2 weeks at 3T using endogenous contrast. Methods: CEST contrast related to proteins at 3.5 ppm (amide proton transfer) and proteins/lipids at −3.5 ppm (relayed nuclear overhauser effect [rNOE]) were examined over 14 days in a collagenase-induced ICH mouse model. Imaging findings were validated with immunohistochemistry based on the ICH neuropathology. We also examined iron-containing phantoms that mimicked iron concentrations in hematoma to ensure the iron will not attenuate the CEST contrast during disease progression. Based on the validity of the CEST contrast of hematoma, we further examined related molecular alterations under iron-chelation treatment with deferoxamine. Results: We observed the temporal and spatial differences of CEST contrasts between rNOE at −3.5 ppm and amide proton transfer at 3.5 ppm, in which the core and perihematoma could be identified by rNOE on day 3 and day 14, and amide proton transfer on day 1, day 7, and day 14. Moreover, we observed a 25.7% significant reduction ( P <0.05) of rNOE contrast after deferoxamine treatment to the ICH mice on day 3, which was not observable in amide proton transfer contrast. Our histology data indicated that rNOE primarily correlated with the myelin pathology, and amide proton transfer could reflect the cellularity increase at hematoma up to day 7. Conclusions: Significant rNOE changes correlated well with histologic findings, especially myelin lipids, and regional characteristics in hematoma indicate the uniqueness of CEST magnetic resonance imaging in monitoring molecular changes during ICH and treatment.